The ATP-binding cassette transporter Cbc (choline/betaine/carnitine) recruits multiple substrate-binding proteins with strong specificity for distinct quaternary ammonium compounds - Chen, Chiliang (Mol Microbiol, 2009)
We identified a choline, betaine and carnitine transporter, designated Cbc, from Pseudomonas syringae and Pseudomonas aeruginosa that is unusual among members of the ATP-binding cassette (ABC) transporter family in its use of multiple periplasmic substrate-binding proteins (SBPs) that are highly specific for their substrates. The SBP encoded by the cbcXWV operon, CbcX, binds choline with a high affinity (K(m), 2.6 μM) and, although it also binds betaine (K(m), 24.2 μM), CbcXWV-mediated betaine uptake did not occur in the presence of choline. The CbcX orthologue ChoX from Sinorhizobium meliloti was similar to CbcX in these binding properties. The core transporter CbcWV also interacts with the carnitine-specific SBP CaiX (K(m), 24 μM) and the betaine-specific SBP BetX (K(m), 0.6 μM). Unlike most ABC transporter loci, caiX, betX and cbcXWV are separated in the genome. CaiX-mediated carnitine uptake was reduced by CbcX and BetX only when they were bound by their individual ligands, providing the first in vivo evidence for a higher affinity for ligand-bound than ligand-free SBPs by an ABC transporter. These studies demonstrate not only that the Cbc transporter serves as a useful model for exploring ABC transporter component interactions, but also that the orphan SBP genes common to bacterial genomes can encode functional SBPs.